University education and technological culture in the knowledge society (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This study analyzes the emergence of Information and Communication Technologies of the educational culture in the Knowledge Society. A reflection is made on the advantages and disadvantages of technologies in the process of education, teachers and students. Likewise, of the new strategies that are used in the classrooms such as flipped classrooms or challenging collaborative tasks that are not linear, but rather resolution of cases where they relate to the family and the community. The relationship between anthropology and technology allows us to investigate and forecast realities based on behaviors. For the development of this investigation a documentary investigation was applied. Likewise, the Analytical Research Summaries (RAI) method was used and adapted, which consists of synthesizing key points of the referenced authors.
Keywords: Higher Education; Knowledge Society; Information Technology; Extended Classroom; Collaborative Tasks